2021
DOI: 10.3389/fmed.2021.676870
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Infection in Pregnancy: Clinical Signs, Placental Pathology, and Neonatal Outcome—Implications for Clinical Care

Abstract: Introduction: The current COVID-19 pandemic has been associated with high rates of mortality and significant morbidity. Both the risk of infection for pregnant women and the risk of vertical transmission have been evaluated, and the presence of the SARS-CoV-2 virus has been demonstrated both in the placenta and in the amniochorionic membranes. However, the actual effects of this pathogen on pregnancy and on placental morphology are still unclear.Objective: To describe histopathologic findings in the placentas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
0
9
1
2
Order By: Relevance
“…Histiocytic intervillositis, syncytial node enlargement, and increased fibrin deposition were all observed at higher rates in SARS-CoV-2 infected placentas, according to a retrospective study conducted in Italy. 132 As a whole, these studies point to a distinctive form of placentitis caused by SARS-CoV-2 infections, which causes extensive placental destruction and increases the risk to the developing fetus. The effect of the recent Omicron variant on pregnancy related complications remains to be determined in ensuing months…”
Section: Placental Histopathologymentioning
confidence: 98%
“…Histiocytic intervillositis, syncytial node enlargement, and increased fibrin deposition were all observed at higher rates in SARS-CoV-2 infected placentas, according to a retrospective study conducted in Italy. 132 As a whole, these studies point to a distinctive form of placentitis caused by SARS-CoV-2 infections, which causes extensive placental destruction and increases the risk to the developing fetus. The effect of the recent Omicron variant on pregnancy related complications remains to be determined in ensuing months…”
Section: Placental Histopathologymentioning
confidence: 98%
“… 9 , 10 Subsequent studies have varied from case reports or small case series to larger studies of around 100 placentas. 11 While some studies re-demonstrated FVM 12 or MVM, 11 others have not demonstrated any significant placental findings in women with SARS-CoV-2 infection. 13 A meta-analysis conducted in the summer of 2021 reported findings suggestive of placental hypoperfusion and inflammation in pregnancies complicated by SARS-CoV-2 infection, 14 while a more recent meta-analysis suggested that there are no typical placental findings.…”
Section: Introductionmentioning
confidence: 99%
“…Серед доступних літературних джерел найбільше дослідження стану плаценти провели S. Moresi та співавт. [34] На відміну від вищевказаного, результати дослідження S. Moresi та співавт. [34] прямо корелювали з виявленими перинатальними ускладненнями.…”
Section: дослідження плаценти у вагітних із Covid-19unclassified
“…[34] На відміну від вищевказаного, результати дослідження S. Moresi та співавт. [34] прямо корелювали з виявленими перинатальними ускладненнями. Такі порушення в плаценті, вочевидь, є наслідком системної запальної реакції та/або гіперкоагуляції, які патогенетично притаманні COVID-19.…”
Section: дослідження плаценти у вагітних із Covid-19unclassified